A Systematic Literature Review on Tax Amnesty in 9 Asian Countries - Ibrahim, Muhammad Alishahdani; Myrna, Rita; Irawati, Ira; Kristiadi, J. B. (International Journal of Economics and Financial Issues, 2017)
Tax amnesty as a part of a fiscal policy has been implemented by either the developed countries and the developing countries as it maximizes the revenue from the unpaid taxes. Nine countries in Asia had implemented tax amnesty: Bangladesh, India, Indonesia, Kazakhstan, Malaysia, Pakistan, Philippines, Sri Lanka, and Thailand. The study aims to examine the implementation of tax amnesty in 9 Asian countries. The data was collected from a literature survey on the scholarly journals and online articles that discuss the implementation of the tax amnesty in each country. The study shows that to have an effective tax amnesty effect, the government should avoid the long-term duration and too frequent tax amnesty program as it would have a detrimental effect on the taxpayer behavior. Keywords: Tax amnesty, implementation, literature review, Asia JEL Classifications: H20, H27, H30, H71